2002
DOI: 10.1055/s-2002-20585
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and Beta Receptor Antagonist Overdose: A Review and Update of Pharmacological Principles and Management

Abstract: Calcium channel and beta-adrenergic receptor antagonists are common pharmaceutical agents with multiple overlapping clinical indications. When used appropriately, these agents are safe and efficacious. In overdose, however, these agents have the potential for serious morbidity. Calcium channel blockers and beta blockers share similar physiological effects on the cardiovascular system, such as hypotension and bradycardia, in overdose and occasionally at therapeutic doses. The initial management for symptomatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 52 publications
0
37
0
7
Order By: Relevance
“…Severe CCB toxicity unresponsive to therapies mentioned above may require cardiac pacing and other advanced therapies such as intra-aortic balloon pump or extracorporeal membrane oxygenation. 61 ␤-Blocker toxicity is still most commonly treated by administering high-dose glucagon therapy. A glucagon bolus of 5 to 10 mg (150 g/kg) over 1 to 2 min is frequently used in this setting.…”
Section: Cardiovascular Medicationsmentioning
confidence: 99%
“…Severe CCB toxicity unresponsive to therapies mentioned above may require cardiac pacing and other advanced therapies such as intra-aortic balloon pump or extracorporeal membrane oxygenation. 61 ␤-Blocker toxicity is still most commonly treated by administering high-dose glucagon therapy. A glucagon bolus of 5 to 10 mg (150 g/kg) over 1 to 2 min is frequently used in this setting.…”
Section: Cardiovascular Medicationsmentioning
confidence: 99%
“…However, in patients with severe hypotension, IV calcium, glucagon, inotropic therapy, high-dose insulin therapy, lipid emulsion, and aortic balloon pump application are other treatments (10,13,14). In our study, IV calcium, hydration with normal saline, and inotropic therapy were administered to the patients with hypotension and with USG-detected peritoneal and pleural free fluid.…”
Section: Discussionmentioning
confidence: 94%
“…The presence of variable amounts of collaterals makes the colon susceptible to ischemia (15). Depending on the CCB overdose, although complicated and surgery-requiring complications such as submucosal edema, ischemia, necrotic ulceration, bleeding, and even gangrene have been observed in case reports in the literature, clinical situations, such as pseudo-obstruction, that can be treated without surgical treatments have also been shown (2,10). In a patient who developed non-occlusive colonic ischemia due to verapamil overdose, Perbet et al (5) found a gangrenous segment in the left column with exploratory laparotomy, and a histopathological examination revealed submucosal edema, necrotic patchy ulceration areas, and intramural hemorrhage due to submucosal vessel dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to intravenous fluids, if necessary, inotropic drugs should be used for hypotension. [1][2][3][4][5][6]9] In certain cases, calcium infusions may improve contractility and hypotension. [10] In our case, we used activated charcoal for intestinal lavage, intravenous fluid, positive inotropic drugs, and intravenous calcium infusion.…”
Section: Discussionmentioning
confidence: 99%